ASEAN and Ongoing Cultural Conflicts - Adriani, Isyana (Universitas Muhammadiyah Yogyakarta, 2014)
This paper analyses ASEAN’s diplomatic style using Hofstede’s theory of Cultural Dilemma Indicators and uses it to explain why the organization has failed to stop on-going cultural conflicts such as the PreahVihear temple dispute. There are 13 cultural dilemma indicators discussed in the paper, each is backed with an example which in the end leads to the conclusion that the government of each ASEAN member state must invest in longterm yet effective solutions. These solutions are necessary since ASEAN is embarking on ASEAN Community (AC), which is slated to take place in 2015, and since this paper is about the organization’s diplomatic style in light of continuing cultural conflicts, the focus is on AC’s Socio-Cultural Community pillar. The recommendations offered in this paper are necessary not only to prepare ASEAN people for major changes AC will bring in the context of culture, but also to rectify ASEAN’s image in the eyes of observers outside Southeast Asia who view the organization as nothing more than a “talk shop.” As a whole, they contribute to a successful ASEAN Community.